(untitled) (Journal of Rangpur Medical College, 2023)
Background: Successful treatment in patients with hypothyroidism depends on adequate knowledge, a positive attitude, and appropriate practices. Deficiency in any domain may lead to the persistence of symptoms, difficulty issues in pregnancy, as well as adverse effects on offspring in female patients. Objective: To evaluate the knowledge, attitude, and practice (KAP) of reproductive-aged adult (18 – 45 years) females with hypothyroidism and their associations with current treatment status. Methods: This cross-sectional questionnaire-based KAP survey was done at seven places across Bangladesh in government hospitals and private chambers among 393 hypothyroid patients [age: 30.0 (25.0-36.0), years, median (IQR)]. Adult females who could read and understand the Bangla language were included. Patients with known dementia, illiterate, severely ill, and unwilling to participate were excluded. The knowledge domain consisted of ten single-best multiple-choice questions (MCQs: 3-4 choices). The attitude domain had five statements with a five-point Likert scale ranging from strongly agree to strongly disagree. The practice domain had also ten single best MCQs (3-5 choices) to assess the patients’ most common practice behaviors. The questionnaire was supplied to each patient and advised to put a tick mark at the appropriate option. Patients’ treatment status was considered by current serum TSH levels (0.4 – 4.0 mIU/mL). Results: The percent of over-replacement, appropriate replacement, and under-replacement was around 12%, 47%, and 41% of the study population respectively. Around 39% had good knowledge, 78% were highly concerned about thyroid disorders, and only 22% were highly cautious about their practice. Age and educational status might be associated with all three domains. Conclusions: More than half of the reproductive-aged adult females’ treatment status was inappropriate. Discrepancies among the three domains might be associated with the age and knowledge status of the participants. The study findings will help clinicians to manage patients with hypothyroidism more efficiently. J Rang Med Col. March 2023; Vol. 8, No. 2:11-19